2021
DOI: 10.3390/ani11113177
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Hepatitis E Virus Type 3 in Switzerland—From Stable to Table

Abstract: Hepatitis E caused by hepatitis E viruses of the genotype 3 (HEV-3) is a major health concern in industrialized countries and due to its zoonotic character requires a “One Health” approach to unravel routes and sources of transmission. Knowing the viral diversity present in reservoir hosts, i.e., pigs but also wild boars, is an important prerequisite for molecular epidemiology. The aim of this study was to gain primary information on the diversity of HEV-3 subtypes present along the food chain in Switzerland, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The most frequent type of co-infections were triple infections with RVA, RVB, and RVC and double infections with RVA and RVC, while RVB and RVC co-infections were rare. This finding is comparable to other studies, where triple infections were reported most frequently (12–21.1%), followed by AC (6.7–24%), BC (3–8%), and AB (5–16%) double infections [ 14 , 17 , 42 , 43 ]. As also reported previously, single infections were mainly caused by RVA, while RVC and, particularly, RVB were rarely observed alone [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The most frequent type of co-infections were triple infections with RVA, RVB, and RVC and double infections with RVA and RVC, while RVB and RVC co-infections were rare. This finding is comparable to other studies, where triple infections were reported most frequently (12–21.1%), followed by AC (6.7–24%), BC (3–8%), and AB (5–16%) double infections [ 14 , 17 , 42 , 43 ]. As also reported previously, single infections were mainly caused by RVA, while RVC and, particularly, RVB were rarely observed alone [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…Due to the low number of samples, it is difficult to conclude on the presence of Swiss subcluster within RV genotypes. However, except for NSP1, NSP2, VP2, and VP3, where most Swiss sequences are closely related, the phylogenetic trees provide no evidence for Swiss-specific subclusters of RVA, as previously observed for other porcine viruses such as hepatitis E virus (HEV) or atypical porcine pestivirus (APPV) [ 43 , 44 ]. In those cases, the high restrictions for the import of living pigs into Switzerland are thought to have favored virus evolution independent from neighboring countries.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Both the ORF 1 and ORF2 regions are used for molecular typing of HEV for Sanger sequencing and NGS, and different subtypes can be determined [ 130 , 225 , 226 , 227 ]. HEV-3 subtypes c, e and f have been shown to be the most prevalent subtypes in Europe [ 4 ].…”
Section: Methods Used For Detection Of Hav and Hev In Different Food ...mentioning
confidence: 99%
“…[11,12] Recent investigations showed that the viral isolates identified in Switzerland are genetically very close, belonging to a specific cluster within genotype 3h, designated here as 3h_s. [4,13,14] This homogeneity reduces the possible impact of viral diversity on clinical phenotype.…”
Section: Introductionmentioning
confidence: 99%